The bank-lending channel empirically revisited - Halvorsen, Jørn I.; Jacobsen, Dag Henning (Journal of Financial Stability, 2016)
This study examines the role of bank equity and bank lending in the monetary transmission mechanism in Norway from January 1993 to August 2008. We apply linear and nonlinear vector-auto-regressive models (VARs) estimated using aggregate monthly data. The results provide support for a “risk-taking channel” in the form of a recasted bank-lending channel running through market-based wholesale funding, in which the impact of monetary policy depends on banks’ financial strength. When banks are weakly capitalized, results based on a nonlinear VAR show a larger monetary-policy effect on real activity.